Picky eating dan status gizi pada anak prasekolah - Hardianti, Rahma; Dieny, Fillah Fithra; Wijayanti, Hartanti Sandi (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2018)
Background : Picky eater tended to reject new or unfamiliar foods. They had preferred food that lead to less food intake diversity. Futhermore, inadequate variation and amount of food intake could distrupt the growth of children.Objective : To determine the correlation between picky eating and nutritional status in preschool children.Methods : This was an observational studies with cross sectional design. Sixty-three subjects were randomly selected based on the inclusion criteria. Data collected included socio-demographic information. Picky eating was obtained through the Children’s Eating Behavior Questionnaire. Nutritional status was measured based on weight-for-height z-score (WHZ), weight-for-age z-score (WAZ), and height-for-age z-score (HAZ).Nutrition intake was assessed by 2x24h dietary recall. Physical activity was obtained using Early Years-Physical Activity Questionnaire. Data were analyzed using Chi-square and Fisher's test.Results : The prevalence of picky eater was 52.4% in preschoolers. WHZ, WAZ, and HAZ mean were -0.3±1.5SD, -0.2±1.3SD, and HAZ -0.2±1.3SD, respectively. Picky eating was associated with carbohydrate and fiber intake (p<0.05). There was no correlation between picky eating and nutritional status of WHZ, WAZ and HAZ (p>0.05). Meanwhile, food intake associated with nutritional status of BB/U was energy, protein and fat intake (p<0.05).Conclusion : There was no relation between picky eating with nutritional status of WHZ, WAZ and HAZ in preschool children.